Clinical outcomes with olanzapine long-acting injection: impact of the 3-hour observation period on patient satisfaction and well-being - Anand E; Berggren L; Landry J; Tóth Á; Detke HC (Neuropsychiatric Disease and Treatment)
Ernie Anand,1 Lovisa Berggren,2 John Landry,3 Ágoston Tóth,4 Holland C Detke5 1Neuroscience Medical Affairs, Eli Lilly & Company Ltd, Windlesham, UK; 2Global Statistical Sciences, Lilly Deutschland GmbH, Bad Homburg, Germany; 3Global Statistical Sciences, Eli Lilly Canada Inc., Toronto, ON, Canada; 4Neuroscience, Lilly Hungary, Budapest, Hungary; 5Psychiatry and Pain Disorders, Lilly Research Laboratories, Eli Lilly and Company, Indianapolis, IN, USA Background: The objective of the present analysis is to determine the impact of the 3-hour observation period for olanzapine long-acting injection (LAI) on patient satisfaction and well-being by comparing data collected before and after its implementation. Methods: This is a post hoc analysis of patients treated with olanzapine LAI in 1) a 6-month fixed-dose randomized controlled trial and/or 2) a 6-year open-label safety study. This analysis was limited to patients with schizophrenia who were treated with olanzapine LAI consistent with the approved indication and dosing recommendations of the European Union Summary of Product Characteristics (N=966). Of the 966 patients, the analysis further focused only on those patients who received both 1) at least one injection before the implementation of the 3-hour observation period and 2) at least one injection after implementation of the 3-hour observation period (N=487). Patient satisfaction was assessed with the three-item Patient Satisfaction with Medication Questionnaire-Modified. Responses were averaged across all postbaseline visits occurring before (ie, without) the implementation of the 3-hour observation period and across all postbaseline visits occurring after (ie, with) the implementation of the 3-hour observation period. In addition, the rate of postinjection delirium/sedation syndrome events was calculated. Results: There was no meaningful change after implementation of the 3-hour observation period in satisfaction (before: mean [SD] =4.0 [1.02] and after: mean [SD] =4.1 [0.82]), preference for olanzapine LAI over oral medication (before: mean [SD] =4.0 [0.90] and after: mean [SD] =4.1 [0.77]), or ratings of satisfaction regarding side effects (before: mean [SD] =1.9 [0.79] and after: mean [SD] =1.8 [0.60]). For the total population (N=966), postinjection delirium/sedation syndrome occurred in 26 (0.07%) of 38,010 injections. Conclusion: For patients with schizophrenia receiving treatment with olanzapine LAI, the 3-hour observation period had no impact on their satisfaction with the medication or on their subjective well-being. Keywords: olanzapine long-acting injection, observation period, schizophrenia, Europe